The Influence of Community Participation, The Role of Village Government, Number of Tourist Visits, and Village Income on Community Welfare in Cibuntu and Citundun Tourism Villages - Sukmana, Eman; Brahmantyo, Himawan; Mumin, Adhi Trirachmadi (Jurnal Penelitian Pariwisata, 2018)
This study aims to analyze the influence of community participation, the role of the village government, the original income from the tourism sector on the welfare of the community in Cibuntu and Citundun Tourism Villages. Data was taken from 100 respondents in each village and using simple random sampling technique. The results show that the village government and the number of tourist visits have a significant effect on the Cibuntu community, while community participation and village original income from the tourism sector have no significant effect. The results of the analysis in Citundun Village showed that the variables of community participation and the role of the village government had a significant effect on community welfare, while number of tourist visits and income from tourism sector did not influence Community welfare. The results of the analysis also showed that the influence of variables under study on community welfare was 21.6%, while the remaining 78.4% was influenced by other variables, not discussed in this study. while in Citundun it was 16.6%, and the remaining 83.4% was influenced by other factors not discussed in this study.